Composite material for diaphragm of acoustic transducer

CN122647873APending Publication Date: 2026-08-28ORA GRAPHENE AUDIO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610234032.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-06-25
Filing Date
2026-02-27
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

正确地合并多个信号是困难的,并且做到这一点的设计往往是昂贵的,同时一些其他设计更具体地针对音频频谱中的孤立部分

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122647873A_ABST
    Figure CN122647873A_ABST
Patent Text Reader

Abstract

There is a composite material for an acoustic transducer diaphragm comprising: a thermoplastic polymer resin, a graphite-based filler, and optionally a coupling agent. The thermoplastic polymer resin is selected from the group consisting of polypropylene, polyethylene, poly(methyl methacrylate), polycarbonate, polyoxymethylene, cyclic olefin copolymer, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyamide, poly(ADP-ribose)polymerase, poly(ethyleneimine), polyamide-imide, poly(ether ether ketone), polyolefin, polyester, polycarbonate, polysulfone, polyacetal, polyvinyl acetal, polyketone, polyamide, cyclic olefin copolymer, thermoplastic thermotropic liquid crystalline polymer, polyphenylene sulfide, polyimide, and mixtures thereof. The graphite-based filler is selected from the group consisting of graphene oxide, reduced graphene oxide, graphite, graphene, and carbon nanotubes, and mixtures thereof. The coupling agent or mixture thereof is selected from the group consisting of titanium organometallic compounds, aluminum organometallic compounds, zirconium organometallic compounds, and silicon organometallic compounds.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This disclosure claims priority to U.S. Provisional Application No. 63 / 763,999, filed February 27, 2025, and U.S. Provisional Application No. 19 / 248,541, filed June 25, 2025, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] This disclosure relates to the field of acoustic transducers, and more specifically to composite materials for acoustic transducer diaphragms. Background Technology

[0004] Microphones typically generate electrical signals from changes in air pressure using electromagnetic induction (dynamic microphones), capacitance changes (condenser microphones), or the piezoelectric effect (piezoelectric microphones). Microphones are typically used in conjunction with preamplifiers before the signal can be amplified by an audio power amplifier for use and / or recording.

[0005] Acoustic transducer diaphragms are used in microphones and speakers to record or transmit sound waves. Microphones generally use electromagnetic induction (dynamic microphones), capacitance changes (condenser microphones), or the piezoelectric effect (piezoelectric microphones) to generate electrical signals from changes in air pressure. Microphones are typically used in conjunction with preamplifiers before the signal can be amplified by an audio power amplifier for use and / or recording.

[0006] Dynamic transducers are electroacoustic transducers that operate on the principle of induction, such as in loudspeakers and microphones. The most common dynamic microphone today is the moving-coil microphone, which utilizes a small, movable induction coil placed in the magnetic field of a permanent magnet attached to a diaphragm. When the diaphragm vibrates under acoustic stimulation, the coil moves within the magnetic field, generating a changing current in the coil through electromagnetic induction. A single dynamic diaphragm does not respond linearly to all audio frequencies, and therefore some dynamic microphones employ multiple diaphragms for different portions of the audio spectrum, subsequently combining the resulting signals. Properly combining multiple signals is difficult, and designs that do so are often expensive; other designs are more specifically targeted at isolated portions of the audio spectrum.

[0007] A loudspeaker, also known as an amplifier, produces sound in response to an electrical signal input. The most common type of loudspeaker today is the moving-coil loudspeaker, which works on essentially the same principle as a moving-coil microphone, but in reverse, its purpose is to produce sound from an electrical signal. When an alternating current audio signal is applied through a voice coil (a coil of wire suspended in a ring-shaped gap between the poles of a permanent magnet), the coil is forced to move rapidly back and forth due to Faraday's law of induction. This causes the diaphragm attached to the coil to move back and forth, pushing air to produce sound waves.

[0008] Therefore, the acoustic performance of microphones and speakers is related to their acoustic diaphragms. Thus, to improve the performance of microphones and speakers, improved acoustic diaphragms are desirable. Summary of the Invention

[0009] In a first aspect of this disclosure, a composite material for an acoustic transducer diaphragm is provided, comprising:

[0010] Thermoplastic polymer resins selected from polypropylene, polyethylene, poly(methyl methacrylate), polycarbonate, polyoxymethylene, cyclic olefin copolymers, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyamide, poly(ADP-ribose) polymerase, polyethyleneimine, polyamide-imide, polyetheretherketone, polyolefin, polyester, polycarbonate, polysulfone, polyacetal, polyvinyl alcohol acetal, polyketone, polyamide, cyclic olefin copolymers, thermoplastic thermotropic liquid crystal polymers, polyphenylene sulfide, polyimide, and mixtures thereof;

[0011] Graphite-based fillers, selected from graphene oxide, reduced graphene oxide, graphite, graphene, carbon nanotubes, and mixtures thereof; and

[0012] Optional coupling agents or mixtures thereof, selected from titanium organometallic compounds, aluminum organometallic compounds, zirconium organometallic compounds, and silicon organometallic compounds, and

[0013] The graphite filler is provided in a weight ratio of 1:99 to 9:1 to the thermoplastic resin.

[0014] In at least some embodiments of the first aspect, the coupling agent is present at a concentration of at least 0.5 wt.%.

[0015] In at least some embodiments of the first aspect, the coupling agent has a chemical structure (R). x -M y -(R') z , where M is selected from silicon, titanium, aluminum, zirconium or a combination thereof, R is a filler-binding functional group, R' is a resin-binding functional group, and the values ​​of x, y and z are defined as 1 ≤ x ≤ 20, 0 ≤ y ≤ 6 and 1 ≤ z ≤ 20.

[0016] In at least some embodiments of the first aspect, the graphite filler is provided at a weight ratio of graphite filler to thermoplastic resin of 1:50 to 9:1.

[0017] In at least some embodiments of the first aspect, the graphite filler is provided at a weight ratio of 200:1 to 2:1 of graphite filler to coupling agent.

[0018] In at least some embodiments of the first aspect, the composite material further comprises an additional filler selected from carbon fibers, cellulose fibers, mineral clays, glass fibers, and combinations thereof.

[0019] In at least some embodiments of the first aspect, the additional filler is provided at a concentration of up to 40 wt.% relative to the total weight of the composite material.

[0020] In at least some embodiments of the first aspect, the composite material has a shape selected from the following:

[0021] • Frustum or inverted truncated cone shape

[0022] • Planar shape,

[0023] • Dome shape or inverted dome shape

[0024] • The central dome portion surrounded by curved edges

[0025] • The central dome portion surrounded by the planar edge portion, or

[0026] • The upper dome section or the lower dome section, and the upper cylindrical section or the lower cylindrical section.

[0027] In at least some embodiments of the first aspect, ribs or stripes are present on the composite material.

[0028] In at least some embodiments of the first aspect, the sound velocity of the composite material is between about 1,500 m / s and 10,000 m / s and the internal loss factor is between 0.001 and 0.5.

[0029] In at least some embodiments of the first aspect, the sound velocity of the composite material is between about 2500 m / s and 7500 m / s and the internal loss factor is between 0.01 and 0.2.

[0030] In at least some embodiments of the first aspect, the difference in sound velocity between the longitudinal and transverse directions of the composite material is 0% to 50%.

[0031] In a second aspect of this disclosure, a method is provided for molding a composite material as defined herein into a shape as defined above, the method comprising thermoforming the composite material into a predetermined shape selected from the shapes listed above. In at least some embodiments, thermoforming is die forming, pneumatic forming, vacuum forming, and / or a combination thereof.

[0032] In a third aspect of this disclosure, an acoustic transducer, such as a loudspeaker or microphone, is provided, comprising a composite material as defined herein.

[0033] In at least some embodiments of the third aspect, the microphone is a dynamic type, with an operating frequency range between 10 Hz and 50 kHz.

[0034] In at least some embodiments of the third aspect, the loudspeaker is a dynamic tweeter with an operating frequency range between 300 Hz and 50 kHz.

[0035] In at least some embodiments of the third aspect, the loudspeaker is a MEMS loudspeaker with an operating frequency range between 10 Hz and 100 kHz.

[0036] In at least some embodiments of the third aspect, the loudspeaker is a balanced armature loudspeaker with an operating frequency range between 10 Hz and 100 kHz.

[0037] In at least some embodiments of the third aspect, the loudspeaker is electrostatic and operates in the frequency range of 10 Hz to 100 kHz.

[0038] In another aspect, a method for manufacturing a graphite-based film is provided, which includes carbonizing a composite material as defined herein at a temperature of 400°C to 2500°C.

[0039] Many additional features and combinations thereof regarding this improvement will become apparent to those skilled in the art after reading this disclosure. Attached Figure Description

[0040] Figure 1A It is the cross-section of a dome-shaped acoustic diaphragm.

[0041] Figure 1B This is an elevation view of a dome-shaped acoustic diaphragm.

[0042] Figure 1C It is the cross-section of an acoustic diaphragm with a central dome shape and an edge.

[0043] Figure 1D It is an elevation view of an acoustic diaphragm with a central dome shape and an edge.

[0044] Figure 1E It is the cross-section of a truncated conical acoustic diaphragm.

[0045] Figure 1F This is an elevation view of a truncated conical acoustic diaphragm.

[0046] Figure 1G It is the cross-section of an acoustic diaphragm with a planar shape and two ribs.

[0047] Figure 1H It is an elevation view of an acoustic diaphragm with a planar shape and two ribs.

[0048] Figure 2 This is a schematic view of a loudspeaker according to one embodiment of the present disclosure.

[0049] Figure 3 This is a box plot showing a comparison of FOM (performance metrics) for acoustic diaphragms with different composite materials.

[0050] Figure 4 It is a graph showing the sound pressure level (SPL) as a function of frequency.

[0051] Figure 5 It is a graph showing the change in torque as a function of the ratio of coupling agent to filler.

[0052] Figure 6 It is a graph showing the change in die head pressure with the ratio of coupling agent to filler. Detailed Implementation

[0053] This document provides composite materials for acoustic diaphragms (also known as acoustic membranes). The composite materials of this application comprise a thermoplastic polymer resin, a graphite filler, and preferably a coupling agent selected from titanium organometallic compounds, aluminum organometallic compounds, zirconium organometallic compounds, and silicon organometallic compounds. It has been found that the combination of thermoplastic polymer and graphite filler improves the performance and cost-effectiveness of the acoustic diaphragm. Furthermore, the addition of the coupling agent as defined herein has been found to improve the acoustic properties of the membrane.

[0054] Coupling agents are reactive molecules that chemically or physically react with fillers / fibers and / or polymer matrices, thereby improving the adhesion between the components of a composite material. In at least some embodiments, the coupling agent has (R) x -M y -(R') z The chemical structure of the compound is given, wherein M is selected from silicon, titanium, aluminum, zirconium, or combinations thereof, R is a filler-binding functional group, and R' is a resin-binding functional group. The values ​​of x, y, and z are defined as 1 ≤ x ≤ 20, 0 ≤ y ≤ 6, and 1 ≤ z ≤ 20. In some embodiments, R is selected from alkoxy, carbonyl, carboxyl, acyloxy, amide, alkeneoxy, and alkeneoxycarboxyl. In at least some embodiments, R' is selected from vinyl, aliphatic epoxyalkyl, styryl, methacryloxy, acryloxy, aliphatic amino, chloropropyl, aliphatic mercapto, aliphatic sulfonyl, isocyanate, aliphatic urea, aliphatic carboxyl, aliphatic hydroxyl, cyclohexyl, phenyl, aliphatic formyl, acetyl, and benzoyl.

[0055] As used herein, the term "graphite-based materials" refers to one or more materials selected from graphene, graphite, graphene oxide, graphene oxide, reduced graphene oxide, and reduced graphene oxide. Similarly, the term "graphite-based oxide materials" refers to one or more materials selected from graphene oxide, graphene oxide, reduced graphene oxide, and reduced graphene oxide. For example, graphite-based materials include graphene oxide, graphite, reduced graphene oxide, graphene powder, graphene nanoplatelets, graphene nanosheets, single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), and their functionalized counterparts and mixtures thereof.

[0056] Graphite exists in the crystalline form of carbon, composed of sp(s) arranged in a hexagonal structure. 2 - The stacking of 2D lattices of hybrid carbon. In its thinnest form, a single layer of graphite hexagonal structure is referred to as graphene. Depending on the context, structures with up to 10 layers, and even in some cases up to 100 layers of hexagonal structure, can still be referred to as graphene, so the boundary between graphite and graphene can be blurred. In this specification, structures with up to 10 layers of graphene are referred to as graphene, while structures with more than 10 layers of graphene will be referred to as graphite. Perhaps due to the difference in thickness between the two, graphite particles are generally referred to as "flakes," and graphene particles as "sheets." Therefore, in some embodiments, the composite material comprises multiple single-layer and / or multi-layer graphene. In some embodiments, the composite material comprises multiple single-layer and / or multi-layer graphite.

[0057] Graphene is a polyaromatic carbon material containing a polyaromatic fused ring system. Graphene is primarily produced through mechanical, liquid, chemical exfoliation, or combinations thereof, of graphitic materials (such as natural graphite, synthetic graphite, and carbon fibers). Alternatively, polyaromatic carbon materials can also be produced by other methods (such as organic carbonization, chemical vapor deposition (CVD), or plasma methods).

[0058] Graphite oxide is a compound composed of carbon, oxygen, and hydrogen in variable proportions. The mass percentage of carbon is typically around 45%, and the typical carbon-to-oxygen ratio can be between 1.8 and 2.9. Natural functional groups on graphite oxide include hydroxyl, epoxy, carbonyl, carboxylic acid, and organosulfate groups. Due to the similarity between the materials, graphene oxide is also a compound composed of carbon, oxygen, and hydrogen in similar proportions to graphite oxide. Graphene oxide materials possess a polyaromatic fused-ring system, where the typical carbon-to-oxygen ratio is between 0.5 and 4. They are produced through chemical or electrochemical oxidation of graphitic materials such as natural graphite, synthetic graphite, and carbon fibers.

[0059] Reduced graphene oxide and reduced graphene oxide are similar to their graphene oxide and graphene oxide counterparts, except that they gain electrons (i.e., they exhibit a decrease in their oxidation state), which is typically achieved through chemical reduction, thermal reduction, photoreduction, hydrothermal reduction, or a combination of different reduction types. Maximal reduction of graphene oxide yields graphene, while maximal reduction of graphene oxide yields graphite.

[0060] As used in this article, the term "carbon nanotube" includes both "single-walled carbon nanotubes" (SWCNTs) and "multi-walled carbon nanotubes" (MWCNTs). SWCNTs are two-dimensional graphene sheets in the form of hollow cylinders. MWCNTs are multiple nested SWCNTs forming concentric tubes.

[0061] Chemically functionalized graphitic materials are those materials that are chemically modified to introduce non-natural chemical groups through covalent or non-covalent bonding (e.g., π-π interactions). This paper envisions the chemical functionalization of the aforementioned graphitic materials.

[0062] The composite material comprises a thermoplastic polymer resin selected from polypropylene, polyethylene, poly(methyl methacrylate), polycarbonate, polyoxymethylene, cyclic olefin copolymers, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyamide, poly(ADP-ribose) polymerase, polyethyleneimine, polyamide-imide, polyetheretherketone, polyolefin, polyester, polycarbonate, polysulfone, polyacetal, polyvinyl alcohol acetal, polyketone, polyamide, cyclic olefin copolymers, thermoplastic thermotropic liquid crystal polymers, polyphenylene sulfide, polyimide, and mixtures thereof.

[0063] Compared to traditional metallic acoustic diaphragms, composite materials comprising graphite-based materials and thermoplastic polymers offer the advantage of lower material costs. Furthermore, this material exhibits improved acoustic performance, particularly with the addition of a coupling agent, as demonstrated in the Examples section below (increased resonant frequency, narrower variation around the resonant frequency, and improved mixing effect between the graphite-based materials and the thermoplastic polymer). However, even without the use of a coupling agent, its performance is still improved in terms of properties compared to conventional acoustic diaphragms, especially in terms of manufacturing costs, offering a cost advantage while achieving similar or better properties.

[0064] In at least some embodiments, the composite material comprises 20 wt.% to 50 wt.% of a graphitic material and 40 wt.% to 80 wt.% of a thermoplastic resin. The graphitic material is provided such that the weight ratio of the graphitic material to the thermoplastic resin is between 1:99 and 9:1, between 1:50 and 9:1, between 1:30 and 9:1, between 1:20 and 9:1, between 1:15 and 9:1, between 1:9 and 9:1, between 1:9 and 3:1, or between 1:9 and 2:1. In the composite material, the graphitic material is a filler and is therefore referred to herein as "graphitic filler". In at least some embodiments, the graphitic filler is provided such that the weight ratio of the graphitic filler to the coupling agent is between 200:1 and 2:1 or between 50:1 and 2:1. In at least some embodiments, the composite material contains at least 0.5 wt.%, at least 1 wt.%, at least 2 wt.%, at least 5 wt.%, or at least 10 wt.% of a coupling agent.

[0065] Optionally, the composite material includes added additional fiber filler selected from carbon fibers, cellulose fibers, microfibrillated cellulose, nanofibrillated cellulose, and glass fibers. The additional fiber filler can be provided at concentrations up to 40 wt.%, up to 35 wt.%, up to 30 wt.%, up to 25 wt.%, and up to 20 wt.% (e.g., 1 wt.% to 40 wt.%, 1 wt.% to 30 wt.%, 1 wt.% to 20 wt.%, 5 wt.% to 40 wt.%, 5 wt.% to 30 wt.%, 5 wt.% to 20 wt.%, or 5 wt.% to 15 wt.%).

[0066] As used herein and throughout this disclosure, "acoustic transducer" refers to a component, device, or element within a device or system for converting an electrical signal into an acoustic signal propagating in a medium and / or converting an acoustic signal propagating in a medium into an electrical signal. Such acoustic transducers may include, but are not limited to, microphones and amplifiers that form part of portable electronic devices (PEDs), portable electronic devices (FEDs), wearable devices, and other devices (e.g., headphones). The composite materials of this disclosure can be used as membranes in acoustic transducers.

[0067] Acoustic transducers can have membranes of various shapes. Therefore, composite materials can be molded into curved or substantially flat membranes. During the manufacturing process, the shape of the membrane is controlled to suit the intended application. Membranes can be made in various thicknesses. Membrane thicknesses can range from micrometers to millimeters to centimeters. In some embodiments, thicknesses are 5µm to 2cm, 5µm to 10mm, or 10µm to 5mm. In some embodiments, multiple membranes are stacked and subsequently bonded together to form a single membrane whose total thickness is greater than the total thickness of the individual membranes constituting it. Bonding of multiple membranes can be achieved by adhesive bonding, thermal bonding, pressing, or a combination thereof. In some embodiments, a method for manufacturing a graphite-based membrane is provided, which involves carbonizing the composite material as described herein at a temperature of 400°C to 2500°C. Heating can be performed in steps. Carbonization can last from 30 minutes to 24 hours.

[0068] Composite materials can be formed using thermoforming processes such as die forming, pneumatic forming, vacuum forming, and / or combinations thereof. This can be used to shape composite materials into frustoconical shapes, inverted frustoconical shapes, planar shapes, dome shapes, inverted dome shapes, shapes having a central dome portion surrounded by curved edge portions, shapes having a central dome portion surrounded by planar edge portions, or shapes having an upper or lower dome portion and an upper or lower cylindrical portion. It is also envisioned that ribs, stripes, or other small features can be added to the shapes described herein. Figures 1A to 1H Exemplary geometries that composite materials can be made are shown. Figures 1A to 1B The diagram illustrates the dome. Figures 1C to 1D The illustration shows a central dome with an edge. Figures 1E to 1F The diagram illustrates a truncated cone, and Figures 1G to 1H The illustration shows a planar diaphragm with two ribs.

[0069] The membrane or acoustic diaphragm (or the composite material itself) made of the composite material of this disclosure can be characterized as having a sound velocity between 1,500 m / s and 10,000 m / s or between 2,500 m / s and 7,500 m / s, and / or can be characterized as having an internal loss factor between 0.001 and 0.5 or between 0.1 and 0.2. In at least some embodiments, the composite material can be characterized as having a sound velocity difference of 0% to 50% between the longitudinal and transverse directions.

[0070] Therefore, it is envisioned that composite materials can be integrated into acoustic transducers, microphones, and loudspeakers. In one example, an acoustic transducer is provided that is dynamic, operating in the frequency range of 10 Hz to 100 kHz or 10 Hz to 50 kHz, with the composite material as the material for the acoustic diaphragm. Other acoustic transducers with different frequency ranges can be fabricated using acoustic diaphragms made from the composite materials disclosed herein. For example, the acoustic transducer may be a dynamic tweeter operating in the frequency range of 300 Hz to 50 kHz, a microelectromechanical system (MEMS) loudspeaker operating in the frequency range of 10 Hz to 100 kHz, or a balanced armature loudspeaker operating in the frequency range of 10 Hz to 100 kHz.

[0071] In one exemplary embodiment, speaker 10 is shown Figure 2 In this exemplary embodiment, a diaphragm 1 made of the composite material of this disclosure is supported by a support material 2, which in turn is supported by a frame 3. The loudspeaker has pole pieces 4 (shown as the south pole in the figure) and a permanent magnet 5 (shown as the north pole in the figure). A coil frame 6 is connected to a voice coil 7 wound around the permanent magnet 5. Electrical leads extend downwards from the diaphragm 1 along the length of the permanent magnet 5 and are connected to the voice coil 7. The electrical leads provide an electrical signal to induce vibration of the diaphragm, thereby emitting sound waves.

[0072] Example

[0073] A composite material wherein 70 parts of polycarbonate (PC) resin are premixed with (with or without) 0.7 parts of a titanate coupling agent and 30 parts of a graphitic filler (graphite or reduced graphene oxide) using a Henschel high-strength mixer. The premixed powder is then transferred to a Barbender twin-screw compounder and extruded at a temperature of 180°C to 265°C. The extrudate is then granulated, and the granulated pellets are fed into a single-screw extruder for film extrusion at 265°C. The extruded film is then further calendered to improve film uniformity and mechanical properties. The calendered film can optionally be biaxially stretched at a temperature of about 150°C to further improve mechanical properties. Alternatively, the resin and filler can be kneaded near the resin's melting temperature and then rolled into sheets.

[0074] To manufacture the transducer assembly, the extruded film (composite material) is thermoformed into a dome shape at around 150°C, and then laser-cut. The formed film is then bonded to a polyurethane support to form a complete transducer diaphragm.

[0075] Table 1 Composition of the tested composite material (CA = coupling agent)

[0076]

[0077] Figure 3 The figure of merit FOM (defined as (E / ρ)) is shown. 3 ) 1 / 2 The comparison is shown, where E is the Young's modulus of the material and ρ is the density of the material. Composites made with titanate coupling agents show a 20% improvement in FOM compared to composites without coupling agents. Figure 4 A comparison of the frequency response of headphone speakers made from different composite diaphragm materials of equal mass is shown in the range of 1000Hz to 4000Hz. Due to its higher FOM, the composite material containing the coupling agent shows an increased resonant frequency and a narrower SPL variation near the resonant frequency. Finally, Figures 5 to 6 The results show that the mixing mill torque and die pressure decreased after the addition of the coupling agent. This indicates improved mixing between the filler and the polymer resin. Without being bound by theory, the improved mixing between the filler and the resin, along with better compatibility, is the primary reason for the improved acoustic response of the composite material with the added coupling agent.

Claims

1. A composite material for an acoustic transducer diaphragm, comprising: Thermoplastic polymer resins selected from polypropylene, polyethylene, poly(methyl methacrylate), polycarbonate, polyoxymethylene, cyclic olefin copolymers, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymers, polybutylene terephthalate, polyamide, poly(ADP-ribose) polymerase, polyethyleneimine, polyamide-imide, polyetheretherketone, polyolefin, polyester, polycarbonate, polysulfone, polyacetal, polyvinyl alcohol acetal, polyketone, polyamide, cyclic olefin copolymers, thermoplastic thermotropic liquid crystal polymers, polyphenylene sulfide, polyimide, and mixtures thereof; and Graphite fillers are selected from graphene oxide, reduced graphene oxide, graphite, graphene, carbon nanotubes, and any combination thereof. The graphite filler is provided in a weight ratio of 1:99 to 9:1 to the thermoplastic resin.

2. The composite material according to claim 1, further comprising a coupling agent selected from titanium organometallic compounds, aluminum organometallic compounds, zirconium organometallic compounds, and silicon organometallic compounds.

3. The composite material according to claim 2, wherein the coupling agent is present at a concentration of at least 0.5 wt.%.

4. The composite material according to claim 2 or 3, wherein the coupling agent has a chemical structure (R). x -M y -(R') z , where M is selected from silicon, titanium, aluminum, zirconium or a combination thereof, R is a filler-binding functional group, R' is a resin-binding functional group, and the values ​​of x, y and z are defined as 1 ≤ x ≤ 20, 0 ≤ y ≤ 6 and 1 ≤ z ≤ 20.

5. The composite material according to any one of claims 1 to 4, wherein the graphite filler is provided in a weight ratio of 1:50 to 9:1 of the thermoplastic resin.

6. The composite material according to any one of claims 1 to 5, further comprising an additional filler selected from carbon fiber, cellulose fiber, mineral clay, glass fiber, and combinations thereof.

7. The composite material of claim 6, wherein the additional filler is provided at a concentration of up to 40 wt.% relative to the total weight of the composite material.

8. The composite material according to any one of claims 1 to 7, having a shape selected from the following: • Frustum or inverted truncated cone shape • Planar shape, • Dome shape or inverted dome shape • The central dome portion surrounded by curved edges • The central dome portion surrounded by the planar edge portion, or • The upper dome section or the lower dome section, and the upper cylindrical section or the lower cylindrical section.

9. The composite material according to any one of claims 1 to 8, wherein the composite material has ribs or stripes.

10. The composite material according to any one of claims 1 to 9, wherein the sound velocity is between 1500 m / s and 10,000 m / s and the internal loss factor is between 0.001 and 0.

5.

11. The composite material according to any one of claims 1 to 10, wherein the difference in sound velocity between the longitudinal and transverse directions is 0% to 50%.

12. A method for molding a composite material as defined in claim 5 into a predetermined shape, said predetermined shape being selected from the shape defined in claim 5, said method comprising thermoforming the composite material into said predetermined shape.

13. The method of claim 12, wherein the thermoforming is die forming, pneumatic forming, vacuum forming, and / or a combination thereof.

14. A method for manufacturing a graphite-based film, comprising carbonizing the composite material as defined in any one of claims 1 to 11 at a temperature of 400°C to 2500°C.

15. A loudspeaker comprising the composite material as defined in claim 1.

16. The loudspeaker according to claim 11, wherein the loudspeaker is a moving coil type and its operating frequency range is between 10 Hz and 50 kHz.

17. The loudspeaker of claim 11, wherein the loudspeaker is a dynamic tweeter with an operating frequency range between 300 Hz and 50 kHz.

18. The loudspeaker of claim 11, wherein the loudspeaker is a MEMS loudspeaker with an operating frequency range between 10 Hz and 100 kHz.

19. The loudspeaker of claim 11, wherein the loudspeaker is a balanced armature loudspeaker with an operating frequency range between 10 Hz and 100 kHz.

20. The loudspeaker according to claim 11, wherein the loudspeaker is electrostatic and its operating frequency range is between 10 Hz and 100 kHz.